Increasing the water use efficiency (WUE) of tomato (S. lycopersicum) via manipulation of the abscisic acid (ABA) biosynthesis pathway - White, Charlotte Anne (2011)
Breeding plants that produce equivalent growth with reduced water input (improved water use efficiency (WUE)) is necessary for sustained future crop production. Water deficit induces redistribution and synthesis of the phytohormone abscisic acid (ABA) thereby restricting transpiration. ABA is synthesised via cleavage of oxygenated carotenoids (xanthophylls). This work involved two approaches and three key ratelimiting enzymes in the ABA biosynthesis pathway: 9-cis-epoxycarotenoid dioxygenase (NCED) β-carotene hydroxylase (BCH); and phytoene synthase (PSY). Increasing ABA production under optimal conditions by overexpressing SlNCED1 has been shown to reduce stomatal conductance and improve WUE. The first approach, part of a larger programme exploring the allelic variation of NCED1 in wild tomato species, describes the introgression of S. galapagense and S. neorickii NCED1 alleles into the cultivated tomato background S. lycopersicum cv. Ailsa Craig. Plants homozygous for SgNCED1, SnNCED1 and SlNCED1 alleles were compared for water use gravimetrically. It was concluded that SgNCED1 and SnNCED1 did not improve WUE.